Rancang Alat Reaktor pada Proses Pembuatan Amonium Nitrat Kapasitas Produksi 150.000 Ton/Tahun - Abdur Rahman Hadrami Hadrami (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2021)
Ammonium Nitrate is a raw material for the manufacture of chemical fertilizers that are needed in the agricultural sector. Sadly. Domestic production of ammonium nitrate is still not able to meet domestic needs, so imports are the solution to meet these needs. Until now there are four general methods that are generally used to produce ammonium nitrate, among which there is the vacuum crystallization method. In the process of making ammonium nitrate with a production capacity of 150,000 tons/year, the reactor acts as a place for reacting raw materials in the form of ammonia and nitric acid. The reaction that occurs is exothermic with an operating pressure of 4.4 atm and a temperature of 60 oC. The reactor used is a mixed flow reactor in the form of an upright cylinder with a standard dished top lid.